Doing gender in a toxic world. Women and freebase cocaine in the City of Buenos Aires (Argentina) - Romo Avilés, Nuria (2015)
Consumption of freebase cocaine in Argentina has been investigated among males but not females. This qualitative study focuses on the complexity of relationships between gender identity and the use of drugs, investigating freebase cocaine as an example in the Metropolitan Area of Buenos Aires, Argentina. In-depth interviews were conducted with female consumers in 2010 the results reveal the different ways in which female identity is constructed in the context of social vulnerability. We identify ways of doing gender and feeling like a woman in a man's world that are associated with a higher risk of violence and exclusion for being female.